Dampak Penyuluhan Keluarga Sakinah oleh Penyuluh Agama Islam Terhadap Proses Pemulihan Narapidana di Lapas Narkotika Langkat - Muhammad Fahri Nasution; Diyan Yusri (Peduli Riset dan Pengabdian Masyarakat, 2024)
This research is entitled the impact of family counseling by Islamic Religious Counselors on the recovery process of prisoners in Langkat Narcotics Prison, The problem of drug abuse, both use and illicit trafficking of narcotics at this time is a problem that is difficult to overcome and is constantly discussed. The research problem is to find out and understand the impact of family counseling by Islamic Religious Counselors on the recovery process of prisoners in Langkat Narcotics Prison, the problem of drug abuse. The research method used in this study is a quantitative method, namely one that focuses on the influence between variables that is objective and relatively short. In addition, as a complement, interviews and sampling were also conducted with several prisoners and prison managers. Based on the results of research conducted by the author, the calculated rxy value of 0.597 shows that the value is in the 0.41 - 0.70 group, which means that between variable X and variable Y there is a moderate or sufficient correlation, so it was found that in the research hypothesis, the author stated that There is a relationship between sakinah family counseling by Islamic Religious Counselors and the recovery process for prisoners in the Langkat Narcotics Prison, which was tested by looking for the correlation index value and was found to be acceptable. So it can be concluded that there is a positive and significant relationship between sakinah family counseling by Islamic Religious Counselors and the recovery process of prisoners in Langkat Narcotics Prison